Infographics: strategies for the development of educational skills in geography - da Silva Melo, José Gustavo; da Silva, Lucas Gabriel; Ferreira de Campos Viana, Luiz Augusto (Revista Ensino de Geografia (Recife), 2021)
Infographics are composite multimodal genres, in which verbal text and image merge. The subject of Geography composes the inventory of the curricular "Subjects" of Basic Education, with the purpose of contributing to the constitution of the participative citizen, promoting in this, the knowledge and organization of the local, national and global space, as well as the interrelations of this with the environment that surrounds it. Therefore, supported by these considerations, this research proposal suggests discussing the potential of using different languages in the learning process of learners, through the construction of infographics within the scope of teaching Geography using digital platforms. The research had as field, 2nd year high school classes, in a city in the interior of Ceará. The study is justified by the need to think about a teaching of Geography that is aligned with the new demands of contemporary society in relation to communication when using various types of languages. The research focuses on a qualitative methodological bias. The study used the deductive method, it is presented in this study the development of a methodological proposal experienced with high school learners in the Geography discipline aimed at the production of infographics through the Canva Digital Platform. The results show that the use and production of infographics combined with a process of educating through research is a resource with many potentials in the learning process of learners by adding variation indifferent languages and symbologies, as well as by enabling various learning styles.